Dehydrated fruit leather from mango pomace - Lim, Dora Marie M.
The possibility of utilizing mango pomace, a fibrous by-product from mango puree extraction, in making dehydrated mango leather was explored. Two types of driers, the solar and cabinet dryer were used, Drying of sweetened and unsweetened samples to a range of 10-15 per cent moisture was done.Base on results of the sensory evaluations, the best mango leather was that which was sweetened to 8 per cent by weight with refined white sugar and cabinet-dried to 60-70°C to 10 per cent moisture content (wet basis). Relative to packaging requirements, sorption isotherm studies revealed that the sweetened-cabinet dried mango leather was most stable and generally acceptable at relative humidities below 47.2 per cent, with the maximum allowable relative humidity at 70.4 per cent.